Comprimento telomérico associado a estresse em crianças: uma revisão sistemática - Coimbra, Bruno Messina [UNIFESP] (2016)
Telomeres are repetitive DNA sequences (T2AG3)n present at the ends of the chromatids and provide stability and protection to the DNA molecular structure. Due to the incapacity of the polymerase enzyme to replicate the DNA molecule in its full extent, the length of the telomeric DNA shortens after each cell division. When telomere length shortens to a critical level, DNA defensive mechanisms lead cells to either a state of arrest (senescence) or apoptosis. There is robust amount of evidence that chronic psychological stress speeds the erosion of telomeres. However, only a limited number of studies primarily focused on the association between stress and telomere length in children, and it is still unclear whether young individuals show signs of cellular aging early in life. We conducted a systematic review of studies that investigated the association between stress and telomeres in groups of children aged from three to fifteen years old. Eleven papers met our criteria. The eligible papers used various methodologies and DNA collection methods. Although unable to perform a meta-analysis, we found a relevant association between stress and telomere shortening in children. Stress induced by adversities and difficulties is probable cause for telomere decline from an early age. We believe that further longitudinal studies with multiple telomere measurements in large groups should be encouraged for better assessment of telomere trajectory in psychologically stressed children.